OH 89: A newly described ~1.8-million-year-old hominid clavicle from Olduvai Gorge - Taylor, Catherine E; Masao, Fidelis; Njau, Jackson K; Songita, Agustino Venance; Hlusko, Leslea J (Peer Community Journal)

(untitled)
Objectives Here, we describe the morphology and geologic context of OH 89, a ∼1.8million-year-old partial hominid clavicle from Olduvai (Oldupai) Gorge, Tanzania. We compare the morphology and clavicular curvature of OH 89 to modern humans, extant apes, and a sample of other hominid fossil clavicles. Materials and Methods Comparative samples include 25 modern human clavicles, 30 Gorilla, 31 Pan, 7 Papio, and five hominid clavicles. Length regression on midshaft size using the extant comparative samples is used to estimate the total length of OH 89. A set of 9 linear measurements are taken from each individual. We also describe a new methodology for measuring clavicular curvature using measurements of sternal and acromial curvature, from which an overall curvature measurement is calculated. A principal component analysis (PCA) and a t-distributed stochastic neighbor embedding (tSNE) analysis are used to compare the morphology of OH 89 with the extant and fossil comparative samples. Results Our new method of measuring clavicular curvature successfully separates the different genera of the extant clavicles. The length estimate and sternal and acromial curve measurements for OH 89 falls within the larger male humans. The PCA shows OH 89 and most of the fossil hominids falling between the modern human and Pan groups, while the t-SNE suggests that OH 89, KSD-VP-1/1, KNM-ER 1808, and OH 48 are more similar to each other than to any of the other groups. This analysis also plots KNM-WT 15000 with the modern humans and Krapina 158 with the Pan individuals. Discussion The OH 89 clavicle derives from an individual of unknown hominid species with a shoulder breadth similar to that of a large human male. The curvature of OH 89 is relatively human-like relative to its length. Our new methodology for measuring clavicular curvature, combined with the utilization of t-SNE analyses and comparison of t-SNE results to PCA results, provides greater separation of genera than previously used methods, and wider use of t-SNE may be useful in paleoanthropological work.